Gradual collective wage bargaining - Dobbelaere, Sabien; Luttens, Roland Iwan (Bonn, 2016)
"This paper presents an alternative implementation of firm-level collective wage bargaining, where bargaining proceeds as a finite sequence of sessions between a firm and a union of variable size. We investigate the impact of such a 'gradual' union on the wage-employment contract in an economy with concave production. In a static framework, the resulting equilibrium is equivalent to the efficient bargaining outcome. In a dynamic framework with search frictions, we demonstrate that gradual collective wage bargaining coincides with all-or-nothing bargaining when bargaining takes place in fictitious time before production."